Design of alternative inhaler system to improve the delivery of inhaled pharmaceutical aerosol (IPA) - Jackson, Wong Hoe Hii
This final year project is about to study a new design of alternative inhaler system that will increase the performance of IPA delivery in term of fluid dynamics characteristics.